Transitions of Student Military Veterans into Engineering Education - Michelle M. Camacho; Susan M. Lord; Catherine Mobley; Joyce B. Main; Catherine E. Brawner (Social Sciences, 2021)
As student veterans transition to four-year institutions from the military, they navigate pathways that are often neither linear nor easy. Using Turner’s theory of liminality, we examine student veterans’ perspectives of the transition from military to civilian life. Interviewees include 60 student veterans from all military branches from four universities in the USA. Student veterans describe successes and challenges as they matriculate into engineering education as transfer students. Analyses of qualitative data yield original findings about the importance of mentors and student veteran networks for fostering student veterans’ educational interests and in promoting their persistence. This study uses a framework of liminality to highlight the bridge between prior military position and a forthcoming reentry into society with a new professional identity as an engineer. In describing their studies, student veterans greatly valued military-learned skills, such as patience, discipline, and technical skills, that give them an advantage in their engineering studies. These findings will be relevant to researchers studying transitions in general and researchers investigating veterans or other populations experiencing transitions. University leaders, including student affairs administrators, faculty members, and others who serve the student veteran community will also benefit from the results.